2013
DOI: 10.1002/cbic.201200714
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Recovery of Aldolase Activity in N‐Acetylneuraminic Acid Lyase by Replacement of the Catalytically Active Lysine with γ‐Thialysine by Using a Chemical Mutagenesis Strategy

Abstract: Chemical modification has been used to introduce the unnatural amino acid γ-thialysine in place of the catalytically important Lys165 in the enzyme N-acetylneuraminic acid lyase (NAL). The Staphylococcus aureus nanA gene, encoding NAL, was cloned and expressed in E. coli. The protein, purified in high yield, has all the properties expected of a class I NAL. The S. aureus NAL which contains no natural cysteine residues was subjected to site-directed mutagenesis to introduce a cysteine in place of Lys165 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…1A). The substrate specificity and stereochemistry of this enzyme is highly malleable through protein engineering and directed evolution (34,35), and we have shown that an enzyme bearing the Nca γ-thialysine (2-aminoethyl cysteine) in place of the catalytic Lys-165 retains activity (36). Here we have explored the effect of introducing Ncas throughout the active site on the reaction catalyzed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1A). The substrate specificity and stereochemistry of this enzyme is highly malleable through protein engineering and directed evolution (34,35), and we have shown that an enzyme bearing the Nca γ-thialysine (2-aminoethyl cysteine) in place of the catalytic Lys-165 retains activity (36). Here we have explored the effect of introducing Ncas throughout the active site on the reaction catalyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation was carried out on a small (2.5 mg) scale under denaturing conditions to ensure the cysteine residue was accessible for modification before the protein was refolded. This procedure was previously shown to generate active, modified, refolded enzyme (36). The conversions of Cys→Dha and Dha→Nca were both monitored by ESI mass spectrometry (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations